2009
DOI: 10.1002/jrs.2293
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectroscopy and DFT calculations of di‐amino acid cyclic peptides. Part I: cyclo(Gly‐Gly), cyclo(L‐Ala‐L‐Ala) and cyclo(L‐Ala‐Gly) in the solid state and in aqueous solution

Abstract: Investigations of the vibrational spectra of cyclo(Gly-Gly), cyclo(L-Ala-L-Ala) and cyclo(L-Ala-Gly) are reported. Raman scattering and Fourier transform infrared (FTIR) spectra of solid-state and aqueous protonated samples, as well as their corresponding N-deuterated isotopomers, have been examined. In addition, density functional theory (DFT) (B3-LYP/cc-pVDZ) calculations of molecular structures and their associated vibrational modes were carried out. In each case, the calculated structures of lowest energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 28 publications
2
21
0
1
Order By: Relevance
“…[83] For example, c-(l-Alal-Ala) in a crystal is puckered, whereas c-(l-Ala-d-Ala) is nearly flat. [83] For example, c-(l-Alal-Ala) in a crystal is puckered, whereas c-(l-Ala-d-Ala) is nearly flat.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[83] For example, c-(l-Alal-Ala) in a crystal is puckered, whereas c-(l-Ala-d-Ala) is nearly flat. [83] For example, c-(l-Alal-Ala) in a crystal is puckered, whereas c-(l-Ala-d-Ala) is nearly flat.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that the cyclic dipeptidic unit is normally quite flexible, and its conformation is very dependent on the amino acid side-chain type and interactions. [83] For example, c-(l-Alal-Ala) in a crystal is puckered, whereas c-(l-Ala-d-Ala) is nearly flat. [84] The peptide ring in the c-(l-Trp-l-Trp) crystal structure is also flat.…”
Section: Dipeptide Ring Geometrymentioning
confidence: 99%
“…Accordingly, the most significant vibrational bands identified through the loadings of the PCA analysis of Raman and DLIPS datasets for classification, including their relative intensity in the Raman or DLIPS spectra were tabulated in Table 1 were more prominent in their respective DLIPS spectra, noting that the band assignments for these shifts can be readily found in the literature for the amino acids and dipeptides. [34][35][36][37][38][39][40][41] The relative intensity differences as well as loading differences of the DLIPS spectral bands as compared to the Raman spectral bands are attributed to differences in the coupling of the excimer laser into various amino acids and dipeptides. It should be highlighted that these intensity differences between DLIPS and Raman spectral bands originated from the perturbative role of the UV light on the molecular bonds with DLIPS, as opposed to traditional vibrational response with Raman.…”
Section: Raman and Dlips Spectramentioning
confidence: 99%
“…The amide I vibration has been found to be heavily dependent on the formation of intramolecular hydrogen bonds in proteins, and hydrogen bonds, in turn, are integral in the stabilization of various protein secondary structures [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. As a result, vibrational spectroscopy combined with density functional theory (DFT) computations is commonly employed to investigate the molecular geometries, dynamics, and secondary structures of short peptide chains [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Navarette and coworkers reported the Raman and IR vibrational spectra for l -glutamic acid [ 44 ], l -aspartic acid (D) [ 35 ], and the glutamic acid (EE) and aspartic acid (DD) dipeptides [ 35 ] in their seminal works and found that these molecules are zwitterio...…”
Section: Introductionmentioning
confidence: 99%